2024
DOI: 10.1021/acsnano.3c10037
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Microenvironment-Activatable Nanoparticle Mediating Immunogene Therapy and M2 Macrophage-Targeted Inhibitor for Synergistic Cancer Immunotherapy

Yuzhu Hu,
Wen Nie,
Liang Lyu
et al.

Abstract: Immunotherapy has achieved prominent clinical efficacy in combating cancer and has recently become a mainstream treatment strategy. However, achieving broad efficacy with a single modality is challenging, and the heterogeneity of the tumor microenvironment (TME) restricts the accuracy and effectiveness of immunotherapy strategies for tumors. Herein, a TME-responsive targeted nanoparticle to enhance antitumor immunity and reverse immune escape by codelivering interleukin-12 (IL-12) expressing gene and colonysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Moreover, the authors demonstrated in vivo, in a mouse transgenic model, the ability of senescent and tumor thyroid cells to recruit and polarize macrophages in the M2-like TAM pro-tumor phenotype and, in turn, TAM allow tumor progression [ 101 ]. Another very recent study demonstrated that the association of the CSF-1R inhibitor, PLX3397 (PLX), with the cytokine IL-12, which has the ability to stimulate the host’s immune activity, promoted repolarization of TAM, stimulated the proliferation and activation of T lymphocytes, reduced MDSCs recruitment, and suppressed tumor growth and metastasis [ 102 ] ( Table 4 ). Cytokines/chemokines are largely produced by CAFs in the TME having a role in the crosstalk between macrophages and cancer cells, as stated above.…”
Section: Re-education Of Tam Towards the Anti-tumor Phenotypementioning
confidence: 99%
“…Moreover, the authors demonstrated in vivo, in a mouse transgenic model, the ability of senescent and tumor thyroid cells to recruit and polarize macrophages in the M2-like TAM pro-tumor phenotype and, in turn, TAM allow tumor progression [ 101 ]. Another very recent study demonstrated that the association of the CSF-1R inhibitor, PLX3397 (PLX), with the cytokine IL-12, which has the ability to stimulate the host’s immune activity, promoted repolarization of TAM, stimulated the proliferation and activation of T lymphocytes, reduced MDSCs recruitment, and suppressed tumor growth and metastasis [ 102 ] ( Table 4 ). Cytokines/chemokines are largely produced by CAFs in the TME having a role in the crosstalk between macrophages and cancer cells, as stated above.…”
Section: Re-education Of Tam Towards the Anti-tumor Phenotypementioning
confidence: 99%